2010
DOI: 10.1103/physrevc.81.054309
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bulk and surface contributions in the neutron skin of nuclei

Abstract: The neutron skin thickness of nuclei is a sensitive probe of the nuclear symmetry energy and has multiple implications for nuclear and astrophysical studies. However, precision measurements of this observable are difficult to obtain. The analysis of the experimental data may imply some assumptions about the bulk or surface nature of the formation of the neutron skin. Here we study the bulk or surface character of neutron skins of nuclei following from calculations with Gogny, Skyrme, and covariant nuclear mean… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(124 citation statements)
references
References 63 publications
(157 reference statements)
8
116
0
Order By: Relevance
“…On the basis of our findings in recent years [30][31][32][33][34], in the next sections we will discuss two of these estimates of the L parameter. Namely, we will study the constraints that can be derived from the analysis of neutron skins in antiprotonic atoms, and the constraints that may be provided by parity-violating elastic electron scattering in a heavy neutron-rich nucleus such as 208 Pb.…”
Section: S(ρ) ≈ E(ρ δ = 1) − E(ρ δ = 0) (3)mentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of our findings in recent years [30][31][32][33][34], in the next sections we will discuss two of these estimates of the L parameter. Namely, we will study the constraints that can be derived from the analysis of neutron skins in antiprotonic atoms, and the constraints that may be provided by parity-violating elastic electron scattering in a heavy neutron-rich nucleus such as 208 Pb.…”
Section: S(ρ) ≈ E(ρ δ = 1) − E(ρ δ = 0) (3)mentioning
confidence: 99%
“…[32,33]. That is, in order to obtain the predictions of the mean-field models for the central radius and diffuseness of the nucleon densities, we fit 2pF functions to the self-consistently calculated nucleon densities of the various models studied in the previous section.…”
Section: Size and Shape Of The Neutron Distribution In 208 Pb And Symmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is commonly defined in terms of the difference between the neutron and proton root-mean-square (rms) radii and is found to be closely related to the density dependence of the NSE, with the EOS of pure neutron matter and properties of neutron stars [39][40][41][42][43][44][45][46]. It is also related to a number of observables in finite nuclei, including the NSE (see, e.g., [4,8,9,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]), although its precise measurement is difficult. As examples, in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Further details of these studies can be found in Refs. [34,35,36,37,38]. Part of the relevance of the extraction of the neutron radius lies on the fact that there exists a nice correlation between the neutron radius in a heavy nucleus such as 208 Pb and the slope of the symmetry energy at saturation L that links an observable of finite nuclei with a property of the symmetry energy.…”
Section: Discussionmentioning
confidence: 99%